2021
DOI: 10.1002/srin.202100388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Initial Columnar‐Grained Inhomogeneity of Electrical Steels on the Transformation Temperature

Abstract: The effects of various initial structures and heating and cooling rates on the columnar‐grained transformation temperature are studied by a thermal dilatometer and electron backscatter diffraction. The results show that deformation can reduce the thermal hysteresis more effectively than decrease the heating rate, and the phase transformation hysteresis of the deformed sample is the smallest during heating, followed by the columnar‐grained sample with a slow heating rate, whereas the columnar‐grained sample wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(17 reference statements)
0
3
1
Order By: Relevance
“…Moreover, it is seen that initial microstructure, rolling reduction, final heating temperature and cooling rate also show their effect and needed to be further optimized. Furthermore, although the silicon content in [1] is as low as 0.35%, much lower than those in this study (0.72-1%Si), according to Thermo-Calc calculation, the addition of high 0.14%P increases its A 1 -A 3 to a higher value than the steels containing 0.64%Si [8] and 2# sheets in this study.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Moreover, it is seen that initial microstructure, rolling reduction, final heating temperature and cooling rate also show their effect and needed to be further optimized. Furthermore, although the silicon content in [1] is as low as 0.35%, much lower than those in this study (0.72-1%Si), according to Thermo-Calc calculation, the addition of high 0.14%P increases its A 1 -A 3 to a higher value than the steels containing 0.64%Si [8] and 2# sheets in this study.…”
Section: Discussioncontrasting
confidence: 64%
“…The commercial products are subjected only to recrystallization annealing in the third stage. Based on our previous quasi-in situ observation of the coarse columnar grains structure in cast slabs, it is confirmed that many columnar grains are retained δ ferrite and the transformation from δ ferrite to austenite is delayed or even suppressed in low-grade electrical steels, showing morphological and texture memory effects of {100} columnar grain structure [1,7,8]. We then suggest a new way of increasing {100} texture in hot-rolled bands to improve magnetic properties of final products, namely the so-called metastable ferrite hot rolling method [7].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations